Ambient Contracts - Harnie, Dries; Scholliers, Christophe; De Meuter, Wolfgang (Electronic Communications of the EASST, 2010)
With current programming languages programmers have to manually keep track of device connectivity state changes while interacting with multiple partners in an ambient environment. This leads to complex code which is hard to evolve and maintain. We propose ambient contracts, a novel programming abstraction which tracks connectivity states in order to react appropriately when failure occurs. With ambient contracts the programmer no longer needs to be concerned about connectivity state changes during interaction, which leads to cleaner code.